Trophoblast biology: Forum introduction - Bazer Fuller W; Spencer Thomas E (BMC, 2004)
Abstract In mammals, a carefully orchestrated dialogue between the mother and conceptus (embryo/fetus and associate extraembryonic membranes) is initiated during the peri-implantation period of pregnancy as the trophoblast develops, functions to signal pregnancy recognition, and initiates implantation. The purpose of this Forum is to highlight comparative aspects of trophoblast morphogenesis and function in mammals.